Sexually Transmitted Infection in Correlation with Cervical Precancerous Lesion - Indarti, Junita; Kurniawan, Riyan H; Nilasari, Hanny (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To identify the correlation between sexually transmitted infection and cervical precancerous lesion. Method: The study design is cross‐sectional. Samples were collected by consecutive sampling method until the minimal amount was fulfilled. This study was conducted in the Colposcopy Outpatient Clinic and Cytology Laboratory, Division of Specialistic Gynecology, Department of Obstetrics and Gynecology, Dr. Cipto Mangunkusumo Hospital (RSCM), Jakarta, from September 2008 to March 2009. Laboratory examination for sexually transmitted infection (STI) was performed in Department of Dermatovenereology, RSCM, Jakarta. Patients were grouped into cases and control group. The case group consisted of patients diagnosed with cervical intraepithelial neoplasia (CIN) and the control group consisted of patients without CIN. Sexually transmitted infection was identified and its relationship to CIN was analyzed. Result: We included 130 patients into this study, 25.38% without CIN and 74.62% with CIN. We found that one patient can be infected by up to five types of infection at a time. We also discovered a statistically significant relation between CIN 1 and STI (p=0.028), CIN 2 and STI (p=0.007), and CIN 3 and STI (p=0.013). Conclusion: Based on our study, we discovered a significant relationship between the incidence of STI and CIN. Keywords: cervical intraepithelial neoplasia, cervical precancerous lesion, sexually transmitted infection